2013
DOI: 10.1371/journal.pone.0077843
|View full text |Cite
|
Sign up to set email alerts
|

Altered Cardiac Electrophysiology and SUDEP in a Model of Dravet Syndrome

Abstract: ObjectiveDravet syndrome is a severe form of intractable pediatric epilepsy with a high incidence of SUDEP: Sudden Unexpected Death in epilepsy. Cardiac arrhythmias are a proposed cause for some cases of SUDEP, yet the susceptibility and potential mechanism of arrhythmogenesis in Dravet syndrome remain unknown. The majority of Dravet syndrome patients have de novo mutations in SCN1A, resulting in haploinsufficiency. We propose that, in addition to neuronal hyperexcitability, SCN1A haploinsufficiency alters car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
146
2
5

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 141 publications
(161 citation statements)
references
References 68 publications
8
146
2
5
Order By: Relevance
“…Auerbach et al (7) reported spontaneous death preceded by bradycardia in 3 Scn1a R1407X/+ mice, and in that study, death was attributed to abnormal intrinsic electrophysiological properties of cardiac myocytes (7). However, breathing was not measured in either the study by Auerbach et al (7) or the study by Kalume et al (40). Here we report postictal bradycardia in Scn1a R1407X/+ mice with a similar time course to that previously reported (7,40), but found that central apnea occurred prior to bradycardia.…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…Auerbach et al (7) reported spontaneous death preceded by bradycardia in 3 Scn1a R1407X/+ mice, and in that study, death was attributed to abnormal intrinsic electrophysiological properties of cardiac myocytes (7). However, breathing was not measured in either the study by Auerbach et al (7) or the study by Kalume et al (40). Here we report postictal bradycardia in Scn1a R1407X/+ mice with a similar time course to that previously reported (7,40), but found that central apnea occurred prior to bradycardia.…”
Section: Discussionsupporting
confidence: 77%
“…However, breathing was not measured in either the study by Auerbach et al (7) or the study by Kalume et al (40). Here we report postictal bradycardia in Scn1a R1407X/+ mice with a similar time course to that previously reported (7,40), but found that central apnea occurred prior to bradycardia. Apnea rapidly causes hypoxemia in mice and rats within seconds (67,68).…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations